Mainstreaming Gender in Water and Sanitation - World Bank (Washington, DC, 2014)
Gender is a concept that refers to socially constructed roles, behavior, activities and attributes that a particular society considers appropriate and ascribes to men and women. A useful definition of the concept of gender mainstreaming is provided by the United Nations Economic and Social Council (1997), suggests that mainstreaming a gender perspective is the process of assessing the implications for women and men of any planned action, including legislation, policies or programs, in all areas and at all levels. It is a strategy for making the concerns and experiences of women as well as men, an integral dimension of the design, implementation, monitoring and evaluation of policies and programs in all political, economic and societal spheres, so that women and men benefit equally and inequality is not perpetuated. The ultimate goal is to achieve gender equality. The chapters that follow highlight in a short summary form experiences of mainstreaming gender at various levels in the water and sanitation sector. It begins with a discussion on gender responses to policy and its requirement for analysis and clear policy objectives to guide operations. The second section touches on experiences of mainstreaming gender within sector operations, beginning with the importance of mainstreaming in the workplace. Section three addresses gender responses to monitoring and evaluation processes, while the fourth section examines responses to gender issues within accountability and voice initiatives. Section five assesses gender responses within hygiene and behavior change programs, while section six examines the linkages between water, sanitation and HIV/AIDS. This is followed by an assessment of the way ahead. In each section good mainstreaming practices are highlighted, while a checklist summarizes key points to consider when mainstreaming gender.